Prediction of the Future Key Features of the Upstream Offshore Wind Power Supply Chain - Jun, Menglong (2013)
Nowadays, significant amounts of studies are carried out on the development of offshore wind power field. This dissertation is motive to focus on this topic likewise. The main purpose of this dissertation is to predict the key features of the upstream offshore wind power supply chain in the future by predicting the trends of the development of every component in the upstream supply chain. The trends that are used for prediction are from the comparisons between the offshore wind power technologies and the land-based wind power technologies. To enhance the quality of the prediction, the offshore wind power supply chain is detailed analyzed. The analysis includes the participators of the supply chain, the opportunities from technologies and the constraints within the supply chain. After analysis, a final conclusion is presented. The conclusion does not only conclude all the findings of previous chapters, but also present the subject of this dissertation. The prediction is that the field is going to locate deeper in the water, equip more advanced machines and systems, develop further and cooperate among participators more comprehensively.